Digital Libraries and Prospects of a Programme on Technology-enhanced Learning in Africa - Islam, Baharul (My University, 2010)
The National Programme on Technology Enhanced Learning (NPTEL) in India is an illustrative project based on the concept of multimedia based courses with high potential for interactivity. It has become a popular and viable option for both developed and developing nations, though for different reasons. Offering multimedia courses in technology-assisted modes has not only become invaluable for the learner, but also an attractive and creative option for faculty. . The broad aim of the project NPTEL in India is to facilitate the competitiveness of Indian industry in global markets through improving the quality and reach of engineering education. The operational objective of NPTEL is to make high quality learning material available to students of engineering institutions across the country by exploiting the advances in information and communication technology. The present paper presents a prospect for such an initiative for African countries and institutions (as potential Associate Partner Institutions) to enhance the quality of human resources in technology and in the arena of the digital library itself.
Keywords: ICADLA, conference, digital library, archive, Development Gateway, e learning